Sistem Peringatan Dari Tindakan Pencurian Mobil Dengan Memanfaatkan Mikrokontroller dan Smartphone - Dwi Dika Lestari; Ade Zulkarnain Hasibuan; Kalvin Chiuloto (UIN Sumatera Utara, 2021)
In today’s increasingly sophiticated era, the crime of car theft is increasing, this is because the warning system installed on the vehicle is steal weak. Another thing that causes car theft is also due to the negligence of the car owner in leaving his car anywhere. For example, leaving the vechicle in a quiet and crime prone place. This is one of the reasons vehicle owners need additional more sophisticated warning systems. By using magnets, hall sensors, buzzers as warning alarms sent via module SIM 800L to vehicle users, it is hoped that this will be a solution in improving the warning system. In thus study, if the tire undergoes 3 rounds in less than 5 second, the buzzer will turn on, thus sending an SMS notification to the user via module SIM 800L which indicates an unwanted movement action on the vehicle. The results of the hall sensor test can detect adjacent magnetic fields, even though there are objects attached to the magnets that do not affect the performance of the hall sensors to detect magnets. These results indicate that the application of magnets and hall sensors affixed to vehicle tires and utilizing module SIM 800L programmed with arduino uno can be one of the right solutions to improve vehicle warning systems. Key words: warning system, hall sensor, arduino